Role of Karṇapuraṇa in Vataja Badhirya w.s.r to Sensory Neural Hearing Loss: A Review Study - Pamnani, Gulab Chand; Sharma, Sanjeev; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Putting medicated lukewarm Swarasa, Taila, Ghrita, Mūtra into the external auditory canal is known as Karnapūraṇa. It is indicated in many diseases like Bādhirya, Karṇa Śūla, Karṇa Nāda, Karṇa Srāva, Putikarṇa etc. Karnapūraṇa can be practised in healthy individuals and disease as well. Snehana is the primary treatment method to control Vāta and Karṇapūraṇa is a kind of Bāhya Snehana. Material and Methods: Ᾱcārya Caraka and Ᾱcārya Vāgbhatta advocated that Karnapūraṇa should be done daily to avoid the diseases of the ear. In Swasthvritīya Adhyāya, Ᾱcārya Suśruta has mentioned Karnapūraṇa. According to use, Karnapūraṇa can be categorised into two categories one as daily procedure (Dincarya) and second in pathological conditions. Discussion: Effect of Abhyanga can be inferred in two ways: a) Through physical manipulations, and b) By the drug’s action in the medicated oil. Massage, produces skin and muscle vasodilation by activating sympathetic nervous system receptors. It improves blood and plasma circulation. Abhyanga relieve acute or chronic muscle tension by changing the pressure of contact on nerve terminals resulting in pain relief. Conclusion: The ears are said to be the seat of Vāta Dośa and are responsible for the hearing mechanism. The disease Bādhirya occurs in ears is mainly due to vitiation of Vāta Doṣa. Karṇapūraṇa does the Vātaśamana and maintains the normal hearing capacity.